The synoptic drivers of extreme rainfall in South Africa - Morison, David (Department of Environmental and Geographical Science, 2014)
A number of studies have shown an increase in the intensity of extreme rainfall over many regions of South Africa during the last 50 to 100 years. However, the weather of a region at any given time is a direct function of the synoptic state of the atmosphere at that particular time. This thesis identifies synoptic states associated with extreme rainfall at a regional scale over South Africa and also investigates trends in extreme rainfall characteristics. Using 31 years of rainfall station data across South Africa, days which experienced extreme rainfall events, defined as the 95th and 99th percentile, were identified. These were then matched against mean sea-level pressure and 500hPa geopotential height circulation patterns obtained from the Climate Forecast System Reanalysis (CFSR) dataset to investigate the driving synoptics of extreme rainfall. Self-organizing maps (SOMs) were used to characterize the synoptic circulations on a general country-wide scale as well as for 8 different regional rainfall regimes at a seasonal scale. Synoptic circulations associated with extreme rainfall events often involved an interaction between more than one synoptic feature such as a linkage between a sub-tropical low pressure system and a mid-latitude cyclone or a ridging high pressure and a continental low pressure. Some features known for contributing towards a significant amount of extreme rainfall events such as cut-off lows in the south-western parts of the country were poorly characterized by the regional SOMs. This may be attributed to the spatial boundaries adopted in this study and suggests general rainfall regimes developed for South Africa are not appropriate for extreme rainfall analyses. Trends in extreme rainfall were assessed in the observed station data with the RClimDex software package and used ten extreme rainfall indices. Apart from the Simple Daily Intensity Index (SDII), which identified a number of significantly increasing trends amongst various stations throughout the country, very few significant trends were identified in the remaining indices. This may be attributed to the infrequent nature of extreme rainfall events and the relatively short 31 year study period. It was, however, discovered that 4 stations with significantly increasing trends in extreme rainfall were paired with synoptic circulations associated with extreme rainfall in the summer rainfall regime that had also experienced significantly increasing trends. Thus the characteristics of extreme rainfall identified in the station data have been associated with the driving synoptic scale circulations and their changing characteristics. However, the generalized regional rainfall regimes identified across South Africa are not appropriate for the study of extreme rainfall synoptic drivers. Here an event-based analysis would provide better insight to the attributes of specific extreme rainfall driving synoptics as well as providing an improved assessment of regional extreme rainfall.